ART AND CULTURE LEARNING IN SUPPORTING CHARACTER EDUCATION FOR EARLY CHILDREN - Feri Faila Sufa; Yetty Isna Wahyuseptiana, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This article describes character education through regional art and culture learning that aims to support decent cities for children. This research uses qualitative research to find out how the implementation of art learning in instilling character education and knowing the factors that hinder and support art learning based on character education. The study was conducted at the Solo Area early childhood education and Boyolali region, using a purposive sampling in early childhood education which was based on regional art and culture learning. The research approach is carried out using an interaction model of qualitative data analysis. The focus of this research is to find the needs of children, supporting and inhibiting factors in art learning in early childhood and this study uses qualitative methods that are analyzed through data collection, data reduction, data presentation, and conclusions or data verification. The results of the research show that learning arts and culture requires exemplary and habitual behavior. Globalization and technological developments are rapidly challenging themselves to create character value for children. Consistency is needed in instilling good character values in the school environment through educators and institutions, family environment and community environment. Early learning is important capital if sustainability can be maintained at a later stage so that decent city children can be implemented based on regional cultural values.